The Effect of Work Motivation on Employee Performance With Job Satisfaction as an Intervening Variable at the Pematang Siantar Branch Office and Tanjung Morawa Branch - SARA KURNIA D SITUMORANG; Mesra B (International Journal of Society and Law, 2024)
This research aims to see the results of the influence of work motivation on employee performance with job satisfaction as an intervening variable at the Pematang Siantar and Tanjung Morawa branch offices. By using quantitative as the type of research, primary data source, questionnaire as data collection technique, the research population was 65 employees and the sample used was also 65 employees with a saturated sampling technique, the research method used was phat analysis with Smart PLS as the calculation tool. The results of this research are as follows: Job Satisfaction has a positive and significant effect on Employee Performance with an original sample value of 0.603 and a p value of 0.000. Work Motivation has a positive and significant effect on Job Satisfaction with an original sample value of 0.842 and a p value of 0.000. Work Motivation has a positive and significant effect on employee performance with an original sample value of 0.348 and a p value of 0.000. Work Motivation has a positive and significant indirect effect on Employee Performance through Job Satisfaction with an original sample value of 0.508 and a p value of 0.000